Thinking with the drone – visual lessons in aerial and volumetric thinking. Issue 5 (19th October 2020) - Jensen, Ole B.
Abstract : This paper set out to do three things: First, it proposes that a given technology (here drones) may prompt scholarly reflections around key ontological dimensions of the world. The advent of drones thus invite urban theorists to 'think with the drone' and reflect upon if our primarily two-dimensional conceptualisation of cities and spaces needs revision. Answering this in the affirmative leads to a need for so-called 'volumetric thinking' as the second task of the paper. The emergence of drones necessitates us to comprehend the 'space between the buildings' and the vertical dimension as key dimension of urban space (which for many still are confined to a simple two dimensional 'flat world' view). This touches upon the third ambition of the paper. By adding a new 'point of view' in a literal sense drones also prompt us to think about aerial visions of the city. How can volumetric thinking be coupled with the new aerial vision in such a way that it enhances our critical understanding of the spatial conditions of cities? The position of this paper is that we need the volumetric 'corrective' not just to counter old habits of 'flat cartographies', but also to prevent the new aerial views opened up by drone technologies to simply become an extension of the 'old two-dimensional view'.